Cloning and identification of genes involved in the interaction between the bacterial stone fruit pathogen Pseudomonas syringae pv. syringae strain NV and plum trees - Appel, Maryke (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2001.